Orientation of the maximum horizontal stress (SHmax) in the Orange basin and Outeniqua sub-basins of South Africa : neotectonic implications - Logue, Andrew Selkirk (Department of Geological Sciences, 2016)
South Africa lies within an intraplate setting, characterised by sparse, scattered, low-magnitude seismicity not easily correlated with known neotectonic features. Recent seismicity has repeatedly been shown to result from the reactivation of pre-existing geological structures, typically large faults or shear zones, which are preferentially-aligned to the contemporary stress field. Expanding the catalogue of stress data for the region is therefore vital to better understand the regional stress field pattern and aid in identifying potentially seismogenic structures. In these intraplate regions, reliable high-quality indicators of maximum horizontal compressive stress (SHmax) are difficult to obtain in the absence of earthquake-derived focal mechanism solutions (so called "beach balls"). In South Africa however, extensive hydrocarbon exploration drilling in the Mesozoic offshore provide an opportunity to utilise the borehole breakout technique to derive quality SHmax orientation data. In collaboration with the World Stress Map Project (WSM), and utilising borehole logs provided by the Petroleum Agency South Africa (PASA), training and software was provided to review, analyse and visualise borehole breakouts observed in 4-arm calliper logs from exploration areas in the Outeniqua and Orange basins. Digital music software can limit the forms of music we create by using interfaces that directly copy those of the analogue instruments that came before. In this study we report on a new multi-touch interface that affords a completely new form of drum sequencing. Based on ideas from Avant-guard music and embodied interaction, a technology probe was created and then evaluated by a wide range of users. We found that for users with no musical training, and for users with a large amount of musical training, the software did allow them to be more creative. However, users with limited training on existing sequencing software found the new interface challenging.